Onset of autumn senescence in High Arctic plants shows similar patterns in natural and experimental snow depth gradients - Gehrmann, Friederike; Ziegler, Camille; Cooper, Elisabeth (Arctic Science, 2021)
Predicted changes in snow cover and temperature raise uncertainties about how the beginning and the end of the growing season will shift for Arctic plants. Snowmelt timing and temperature are known to affect the timing of bud burst, but their effects on autumn senescence are less clear. To address this, researchers have examined senescence under natural and experimental environmental gradients. However, these approaches address different aspects of plant responses and the extent to which they can be compared is poorly understood. In this study, we show that the effect of snowmelt timing on the timing of autumn senescence in High Arctic plants is the same between a natural and an experimental gradient in three out of four studied species. While the two approaches mostly produce comparable results, they give in combination greater insight into the phenological responses to predicted climate changes. We also showed that a short warming treatment in autumn delayed senescence by 3.5 days in Dryas octopetala L., which is a 10% extension of the growing season end for this species. Warming treatments have commonly been applied to the whole growing season, but here we show that even isolated autumn warming can be sufficient to affect plant senescence. Les changements prévus dans la couverture de neige et la température soulèvent des incertitudes quant à la façon dont le début et la fin de la saison de croissance se déplaceront pour les plantes arctiques. On sait que la date de la fonte des neiges et la température influent sur le moment du débourrement, mais leurs effets sur la sénescence automnale sont moins clairs. Pour y répondre, les chercheurs ont examiné la sénescence sous des gradients environnementaux naturels et expérimentaux. Cependant, ces approches abordent différents aspects des réponses des plantes et la mesure dans laquelle elles peuvent être comparées est mal comprise. Dans cette étude, les auteurs montrent que l’effet du moment de la fonte des neiges sur le moment de la sénescence automnale des plantes ...